2012 Asia Pacific Microwave Conference Proceedings 2012
DOI: 10.1109/apmc.2012.6421593
|View full text |Cite
|
Sign up to set email alerts
|

Wave propagation simulations for considering the installation of the maritime mobile satellite communication antennas

Abstract: In maritime mobile satellite communications, received satellite signal level varies due to direction and motion of a ship. Then sometimes the communications are interrupted, because the receiving satellite signal level decreases when the ship's body shadows the antenna. Thus it is important to evaluate how qualities of satellite communications vary during ship operations. However, precise temporal level fluctuations during ship movement are not yet studied. In this paper, to evaluate temporal variances of rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In [31], Chinese first mobile satellite communications system, Tiantong-1, as China's first mobile satellite communications system [31], can provide voice, short message, and low-speed data services, with a peak rate of 9.6 kbps. In [32], high throughput is achieved by satellite EchoStar-19. However, satellite-based communications are easily affected by climate and the marine environment, resulting in low reliability.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In [31], Chinese first mobile satellite communications system, Tiantong-1, as China's first mobile satellite communications system [31], can provide voice, short message, and low-speed data services, with a peak rate of 9.6 kbps. In [32], high throughput is achieved by satellite EchoStar-19. However, satellite-based communications are easily affected by climate and the marine environment, resulting in low reliability.…”
Section: Related Workmentioning
confidence: 99%
“…1) Channel between SSs and OSs: As recommended by ITU, for point-to-area communication with a frequency range from 30 MHz to 4000 MHz, the channel model is widely used for terrestrial and offshore wireless communication [6], [32] and is shown as follows.…”
Section: B Channel Modelsmentioning
confidence: 99%
“…Typical satellite tracking systems described above have fluctuation of only ±0.2 • in angle [13] [18]. According to our previous study, using such tracking systems cause very low level deviation by sea waves or winds compared to level variation by ship headings [9]. Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Qualities of maritime communications are affected by various factors. Our research group has reported fluctuations of received levels in maritime satellite communications due to vibrations of the sea waves or by shadowing with a ship body [9][10] [11]. Satellite antennas on ships usually have an antenna isolation and tracking mechanism, which chases the aiming satellite against movements and vibrations of the ship caused by sea waves or winds [12] [13].…”
Section: Introductionmentioning
confidence: 99%